2018
DOI: 10.1108/jocm-08-2017-0300
|View full text |Cite
|
Sign up to set email alerts
|

Emerging organizational parameters and their roles in implementation of organizational change

Abstract: Purpose The purpose of this paper is to investigate new emerging organizational parameters and their roles in successful change implementation. These organizational parameters are rarely investigated especially in the context of organizational change (OC) in private and public sector organizations. Design/methodology/approach In cumulative, 403 valid responses have been obtained randomly from public sector workers by using self-administered questionnaires. Findings The results reveal that knowledge sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(147 citation statements)
references
References 82 publications
(109 reference statements)
3
128
0
Order By: Relevance
“…Nevertheless, the application of a change model does not ensure the success of the organizational transformation. Various authors have presented a wide variety of causes of failures of organizational change efforts (Appelbaum, Cameron, Ensink, Hazarika, Attir, Ezzedine et al, 2017;Aslam et al, 2018). Their studies have shown that most of the causes have strong correlations between them.…”
Section: Organizational Change Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the application of a change model does not ensure the success of the organizational transformation. Various authors have presented a wide variety of causes of failures of organizational change efforts (Appelbaum, Cameron, Ensink, Hazarika, Attir, Ezzedine et al, 2017;Aslam et al, 2018). Their studies have shown that most of the causes have strong correlations between them.…”
Section: Organizational Change Literature Reviewmentioning
confidence: 99%
“…Not following an organizational change procedure. As previously introduced, organizational transformations are not easy processes and there is no shortage of authors reporting unsuccessful cases (Aslam et al, 2018). To have better chances of success a methodology should be well-defined, alienated with the business structure and executed properly (Attaran, 2000;Brisson-Banks, 2010;Rajan & Ganesan, 2017).…”
Section: Organizational Change Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of Internet and social media, the nature of communications has drastically changed between marketers and customers from one-way to two-way communication [1]. In this sense, social media networks have become significantly developed platforms for businesses to use to perform their activities and achieve their goals [2,3]. In addition, social media platforms are also an important tool for marketers to understand customers' motivations to express and share their needs and wants [4].…”
Section: Introductionmentioning
confidence: 99%